Analisis Keberlanjutan serta Pengaruh Surat Berharga Negara dan Faktor Lainnya terhadap Pertumbuhan Ekonomi di Indonesia - Bambang Juanda; Syadza Gladiola (Direktorat Jenderal Perbendaharaan, Kementerian Keuangan, 2022)
Government Securities (SBN) is one of the instruments that dominates in financing the deficit in the State Revenue and Expenditure Budget (APBN) in Indonesia. This is in line with the government's efforts to continuously improve financial independence. The purpose of this study is to analyze the effect of SBN and other factors on economic growth through government spending, and the condition of debt sustainability in Indonesia using data for the period 2004-2019. The analytical method used in this study uses a simultaneous equation model. The increase in SBN has a significant positive effect in increasing the types of capital expenditures and TKDD expenditures. SBN did not increase subsidies and personnel spending. Capital spending has a significant effect on economic growth with the highest elasticity among other significant government spending. Indonesia's debt condition tends to show a sustainable debt condition, because an increase in SBN is followed by an increase in the primary balance, through productive capital expenditures, thereby increasing growth and state revenues.